Effect of counseling on sexual function and behavior in postmenopausal women and their spouses: a randomized, controlled trial (RCT) study - Tiznobek, Azita; Mirmolaei, Seyedeh Tahereh; Momenimovahed, Zohreh; Kazemnejad, Anooshirvan; Taheri, Safoura (Menopause Review/Przegląd Menopauzalny, 2017)
Sexual dysfunction is present the most important problem among menopausal women and thus counseling may have a major role for improving menopausal sexual state in this population. We aimed to assess effects of counseling on sexual function of menopause women and their spouses. An interventional trial study was performed on 120 consecutive Iranian couples (menopause women and their spouses) who were resident in Hamadan, Iran in 2015. The subjects were randomly assigned to receive counseling service (n = 60) or did not receive this service (n = 60). Couples were asked to complete a standardized validated questionnaire assessing sexual function and behaviors. The frequency of sexual intercourse was considerably increased following first and second counseling sessions compared with the time before counseling in former group, while sexually state was remained unchanged in those who not received these counseling. Furthermore, dyspareunia in interventional women with counseling was significantly reduced after the first and second counseling, whereas this complaint was not significantly removed in the control group within the study period. Also, unsuccessful intercourse was significantly decreased in men who received counseling sessions, while this parameter was remained unchanged in other men. In addition, talking with the partner about sexually and Satisfaction degree of wife’s love was significantly improved in both men and women in interventional groups compared with the control groups. Active and structured counseling effectively improve sexual functions and behaviors in menopausal women and their spouses.